Penerapan P5 dalam Membentuk Karakter Kewirausahaan Melalui Kegiatan Festival Food di SDIT Al Hikmah Depok - Ramdhani, Rahmat; Kurniawati , Hartin (JURNAL KAJIAN ISLAM MODERN, 2023)
The purpose of this study is to determine the effectiveness and efficiency of the application of entrepreneurial character values, teachers can help students apply creative values so that they are able to produce products with high selling power. This research is a qualitative research "case study". The subjects of the study were grade IV students of SDIT Al Hikmah Depok totaling 109 students. Data sources from teachers, data, and documents. Data collection techniques are by observation, interviews, and documentation. Data validity techniques use triangulation of data sources. Data analysis uses descriptive analysis techniques and qualitative analysis techniques. The conclusion of this study is the application of P5 in shaping entrepreneurial character through Food Festival activities. The results of the study are: 1. Effectiveness and efficiency of the application of creative values, 2. Teachers can assist students in applying creative values, 3. Increase high selling power. The conclusion of the results of research conducted at SDIT AL Hikmah Depok using a case study approach got good results. Students have been able to apply entrepreneurial character values, namely creative in the activities of the Food Festival.